David William Foster. El Eternauta, Daytripper, and Beyond: Graphic Narrative in Argentina and Brazil. Austin: U of Texas P, 2016. - Laura M Fernandez (Studies in 20th & 21st Century Literature, 2017)
Review of David William Foster. El Eternauta, Daytripper, and Beyond: Graphic Narrative in Argentina and Brazil. Austin: U of Texas P, 2016.
Keywords: Comics; Brazil; Argentina; Latin American studies; history; sexuality; gender; semiotics